Medical Qigong for Mobility and Balance Self-Confidence in Older Adults - Stahl, James E.; Belisle, Shoshana S.; Zhao, Wenyan (Frontiers in Medicine, 2020)
BACKGROUND/OBJECTIVES: Physical inactivity, sedentary lifestyle, and impaired neuromuscular function increases fall risk and fractures in our aging population. Mind-body modalities, improve strength, balance and coordination, mitigating these risks. This study examined whether a manualized Medical Qigong protocol measurably improves balance, gait, and health self-confidence among older adults. DESIGN: Randomized prospective cohort pre-post study with wait time control. SETTING: Two martial arts centers in Massachusetts and Arizona. PARTICIPANTS: Ninety-five adults age ≥ 50 (mean age 68.6 y.o., range 51 - 96) were randomly assigned to an immediate start group (N=53) or four-week delayed start group (N=43). INTERVENTION: A 10 form qigong protocol taught over 12 weekly classes. MEASURMENTS: Primary outcome measures were the Community Balance and Mobility Scale (CBMS) and Activities-Specific Balance Confidence (ABC) Scale. Data was collected at baseline, one-month and four-months. RESULTS: Both groups at both sites demonstrated improved balance and gait (CBMS + 11.9 points, p< .001). This effect was strongest in patients in their 60s (CBMS +12.9 p <.01) and 70s (CBMS + 14.3, p<.001) , was equal across genders and socioeconomic status. Balance self-confidence did not significantly change (ABC + .9, p=.48), though several elements within ABC trended towards improvement (e.g., walk up/down ramp (p=.07), bend over/pick up (p=.09)). Falls in the past year was inversely correlated with balance self-confidence. (p=.01). CONCLUSION: A 12-week manualized Medical Qigong protocol significantly improved balance and gait and modestly improved balance self-confidence among older adults. Medical Qigong may be a useful clinical intervention for older adults at heightened risk for falls and related injuries.